Design Strategies and Control Methods for a Thermally Driven Heat Pump System Based on Combined Cycles - Al-Tameemi, Mohammed Ridha Jawad; Liang, Youcai; Yu, Zhibin (Frontiers in Energy Research, 2019)
Heating sector is one of the key emitters of greenhouse gas, and thus innovations are needed to improve the energy efficiency of heating technologies. In this paper, a recently proposed gas fuelled heat pump system that integrates an Organic Rankine Cycle (ORC) with an air-sourced heat pump (ASHP) has been further investigated. The heat produced by the gas burner is used to drive an ORC power system to produce mechanical power, which is then directly used to drive a vapour compression heat pump. Two different designs of the combined system were modelled, and their performances were compared and analysed. In the first design, the cold water is firstly heated in the heat pump condenser and then further heated in the ORC condenser to achieve the required final temperature. In the second design, the water is firstly heated in the ORC condenser and then further heated in the heat pump condenser. The results showed that the first design can achieve better overall fuel-to-heat efficiency. Using Aspen Plus, a dynamic model has then been developed to study the optimal control strategies for this design when ambient air temperature changes. The results revealed that, for the ambient temperature ranging from 7 ˚C to 15 ˚C, increasing air mass flow rate is sufficient to maintain the overall system performance. While when ambient temperature is below 7 ˚C, more heat is required from the gas burner that would reduce the fuel-to-heat efficiency.